2012
DOI: 10.1016/j.molcel.2012.07.015
|View full text |Cite
|
Sign up to set email alerts
|

The Seed Region of a Small RNA Drives the Controlled Destruction of the Target mRNA by the Endoribonuclease RNase E

Abstract: SummaryNumerous small non-coding RNAs (sRNAs) in bacteria modulate rates of translation initiation and degradation of target mRNAs, which they recognize through base-pairing facilitated by the RNA chaperone Hfq. Recent evidence indicates that the ternary complex of Hfq, sRNA and mRNA guides endoribonuclease RNase E to initiate turnover of both the RNAs. We show that a sRNA not only guides RNase E to a defined site in a target RNA, but also allosterically activates the enzyme by presenting a monophosphate group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
209
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 201 publications
(224 citation statements)
references
References 57 publications
7
209
2
Order By: Relevance
“…We propose that the OxyS structural changes induced by Hfq create a more preferable RNase E cleavage site, such that degradation of OxyS is enhanced. Recent studies involving MicC, an sRNA that pairs to its mRNA target in the coding region and functions in its down-regulation, indicate that the role of processed MicC (containing a 5 ′ monophosphate) is to guide and activate RNase E to cleave its paired target mRNA leading to mRNA signal removal (Bandyra et al 2012). However, if processed MicC fails to pair to its target mRNA, MicC enters a discard pathway in which it is rapidly degraded by RNase E in the presence of Hfq (Bandyra et al 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We propose that the OxyS structural changes induced by Hfq create a more preferable RNase E cleavage site, such that degradation of OxyS is enhanced. Recent studies involving MicC, an sRNA that pairs to its mRNA target in the coding region and functions in its down-regulation, indicate that the role of processed MicC (containing a 5 ′ monophosphate) is to guide and activate RNase E to cleave its paired target mRNA leading to mRNA signal removal (Bandyra et al 2012). However, if processed MicC fails to pair to its target mRNA, MicC enters a discard pathway in which it is rapidly degraded by RNase E in the presence of Hfq (Bandyra et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…RNase E is known to preferentially cleave 5 ′ monophosphorylated RNA substrates (Mackie 1998), and recent studies have suggested that processing to form 5 ′ monophosphorylated RNAs, potentially via the action of RppH, a pyrophosphohydrolase (Deana et al 2008), may be important for an RNase E-dependent sRNA degradation pathway (Bandyra et al 2012). Consequently, RprA and OxyS were tested in 5 ′ monophosphorylated form.…”
Section: Hfq Impact On Rna Stabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…The coding sequence of Salmonella ompD mRNA contains the binding sites of four sRNAs, which are RybB , SdsR (Frohlich et al 2012), InvR , and MicC (Pfeiffer et al 2009). Among them RybB sRNA represses the initiation of translation , while MicC induces the accelerated decay of ompD mRNA, which is dependent on RNase E (Pfeiffer et al 2009;Bandyra et al 2012). The coimmunoprecipitation studies showed that ompD mRNA was bound by Hfq (Sittka et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…SdsR anneals to ompD mRNA outside of the footprint of the initiating ribosome and is expected to affect mRNA decay rather than translation initiation (Frohlich et al 2012). In contrast, the mode of action of MicC was proposed to involve the recruitment of RNase E to its binding site in mRNA leading to the accelerated decay of ompD mRNA (Pfeiffer et al 2009;Bandyra et al 2012). The fact that Hfq facilitates the annealing of sRNAs acting differently on translation (Table 2; Fig.…”
mentioning
confidence: 99%